Exploration of the Concept and Path of Traditional Chinese Medicine Health Culture Leading the "New Healthy Lifestyle" - Qiu, Jiatian (Journal of Contemporary Medical Practice, 2024)
This paper deeply analyzes the connotation of traditional Chinese medicine health culture and the "new healthy lifestyle", and explores how the concepts of "harmony between man and nature", "balance of yin and yang", "syndrome differentiation and treatment", and "holism" in traditional Chinese medicine health culture meet the needs of modern healthy living. This article elaborates on the practical path of traditional Chinese medicine health culture leading the "new healthy lifestyle" from the aspects of diet regulation, exercise, emotional regulation, and daily routine. It proposes to construct a guarantee system for the integration of traditional Chinese medicine health culture into modern life through education popularization, social promotion, policy support, and other means, aiming to provide theoretical basis and practical guidance for promoting national health.